Unexpected reaction of “wild-type” gastrointestinal stromal tumor to imatinib: case report and literature review - He, Yang; Da, Mingxu; Fan, Chuanlei; Tao, Pengxian (Frontiers in Oncology, 2024)
Background: Most of gastrointestinal stromal tumor (GIST) are driven by mutations in the KIT/PDGFRA genes and can benefit from TKIs treatment. However, a small subset of GIST (10%-15%) are called "wild-type" GIST due to the lack of these mutations. Theoretically, they would not benefit from TKIs treatment and may even develop resistance. Therefore, this unexpected response may challenge inherent perceptions. Herein, we present a case of giant wild-type GIST exhibiting an unexpected response to imatinib(IM), followed by laparoscopic surgical resection. Subsequently, potential underlying mechanisms are discussed.Case Description: This case describes a 57-year-old man who presented with abdominal pain for two weeks. CT revealed a massive lesion near the splenic hilum along the greater curvature of the stomach, concurrently involving the splenic hilar vessels and surrounding lymph nodes. Ultrasoundguided fine needle aspiration biopsy confirmed it is a mesenchymal spindle cell tumor,GIST. Due to the enormous volume and local invasion, neoadjuvant chemotherapy was initially considered. After 6 months of IM 400 mg/d, CT imaging revealed marked changes in tumor heterogeneity and a significant reduction in volume. Subsequently, laparoscopic surgical resection was performed.Postoperative pathological examination, immunohistochemistry, and genetic testing collectively confirmed it is a wild-type GIST.The patient recovered well and was discharged on the 6th day after surgery, with continued oral IM(400 mg/d) after discharge. No recurrence was observed during follow-up until the publication of this report.This unexpected response suggests that wild-type GIST may benefit from TKIss treatment, and the potential mechanisms warrant further investigation. Additionally, true wild-type GIST may not be discerned due to current limitations of Next-Generation Sequencing(NGS).Therefore, for advanced/high-risk GIST, additional genetic analysis can be performed after negative NGS results.